Almost Periodic Solution for an Epidemic Prey-Predator System with Impulsive Effects and Multiple Delays - Baodan Tian; Ning Chen; Yanhong Qiu (Discrete Dynamics in Nature and Society)
A nonautonomous epidemic prey-predator system with impulsive effects and multiple delays is considered; further, there is an epidemic disease in the predator. By the mean-value theorem of multiple variables, integral inequalities, differential inequalities, and other mathematical analysis skills, sufficient conditions which guarantee the permanence of the system are obtained. Furthermore, by constructing a series of Lyapunov functionals it is proved that there exists a unique uniformly asymptotically stable almost periodic solution of the system.